A catalyst for olefin polymerization and its application

By introducing silicone compounds and compounds of general formula (I) into olefin polymerization catalysts, combining titanium, magnesium and organoaluminum compounds, the existing catalysts have a high melt index under high hydrogen conditions and a low melt index under low hydrogen conditions. The problem is that the performance balance is achieved under different hydrogen-ethylene ratios, the activity and copolymerization performance of the catalyst are improved, and it is suitable for the production of bimodal tandem products.

CN116606390BActive Publication Date: 2025-01-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202210121031.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-02-09
Publication Date
2025-01-07
Estimated Expiration
2042-02-09

AI Technical Summary

Technical Problem

The existing olefin polymerization catalyst has a high melt index under high hydrogen conditions and a low melt index under low hydrogen conditions, making it difficult to meet the demand for bimodal tandem products in industrial production.

Method used

Introducing silicone compounds as internal electron donors and compounds of general formula (I) as external electron donors in olefin polymerization catalysts, combining titanium, magnesium and organoaluminum compounds, optimize the composition and preparation process of the catalyst to be high in hydrogen- The melt index is increased under the ethylene ratio and the melt index is maintained at the low hydrogen-ethylene ratio.

Benefits of technology

The balance between high melt index under high hydrogen-ethylene ratio and low melt index under low hydrogen-ethylene ratio is achieved, which improves the activity and copolymerization performance of the catalyst, and is suitable for the production of bimodal tandem products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116606390B_ABST
    Figure CN116606390B_ABST
Patent Text Reader

Abstract

The present invention provides an olefin polymerization catalyst and its application. The olefin polymerization catalyst comprises: (A) a catalyst solid component, the catalyst solid component comprises titanium, magnesium and an internal electron donor, the internal electron donor comprises a silicon ester compound; (B) a co-catalyst component, the (B) co-catalyst component is at least one organic aluminum compound; and (C) an external electron donor, the external electron donor comprises a compound represented by formula (I). When the olefin polymerization catalyst of the present invention is used for ethylene polymerization, it exhibits high catalytic activity, more suitable hydrogen adjustment sensitivity, simple preparation process, and is very suitable for a double-kettle or multi-kettle series ethylene slurry polymerization process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of olefin polymerization catalysis, in particular to an olefin polymerization catalyst and application thereof. Background Art

[0002] After nearly 60 years of development, Ziegler-Natta polyethylene catalysts have made great progress in terms of activity, bulk density of powders, fine powder content, oligomers, etc., and basically meet the requirements of existing industrial production. With the development of new products, when producing bimodal resin products, existing catalysts need to add a large amount of hydrogen, which can easily cause problems such as reduced catalyst activity, severe ethylene ethane reaction, affecting the safe and stable production of the device, and unstable product quality. In order to better meet the needs of industrial production and produce resin products with better performance, it is necessary to provide catalyst products with excellent hydrogen adjustment performance while ensuring the basic performance of existing catalysts.

[0003] In the prior art, introducing some electron donors into olefin polymerization catalysts can improve the hydrogen regulation performance of the catalyst, such as the Chinese patents with publication numbers CN1958620A and CN103772536A, which respectively introduce silane electron donors and benzoate electron donors. Introducing other electron donors can improve the copolymerization performance of the catalyst, such as the Chinese patents with publication numbers CN1726230A, CN1798774A and CN101050248A, which respectively introduce electron donors such as alcohols, ketones, amines, amides, nitrile, alkoxysilane, aliphatic ethers and aliphatic carboxylates. Introducing certain electron donors into the catalyst can improve the activity of the catalyst, such as the Chinese patent with publication number CN102977232A, which introduces halogenated alkanes.

[0004] The electron donors mentioned above can only improve the performance of olefin polymerization catalysts in a certain aspect, which can no longer meet the needs of industrial production. It is necessary to find a type of electron donor that can not only improve the high melt index performance of polyolefin catalysts under high hydrogen conditions, but also maintain the low melt index performance under low hydrogen conditions, so as to meet the needs of industrial production equipment to produce dual-peak series grade products. Summary of the invention

[0005] In order to solve the above problems existing in the prior art, the present invention provides a catalyst for olefin polymerization, and specifically relates to an olefin polymerization catalyst and application thereof.

[0006] The inventors have found through research that when a silicon ester compound is introduced as an internal electron donor and a compound of the general formula (I) is introduced as an external electron donor during the preparation of an olefin polymerization catalyst, the olefin polymerization catalyst can not only show good activity and copolymerization performance, but also show a high polymer melt index under polymerization conditions of a high hydrogen-ethylene ratio (e.g., hydrogen partial pressure: ethylene partial pressure ≥ 3) and a low polymer melt index under polymerization conditions of a low hydrogen-ethylene ratio (e.g., hydrogen partial pressure: ethylene partial pressure ≤ 1). Based on this finding, the present invention is proposed.

[0007] In order to achieve the above object, the present invention provides an olefin polymerization catalyst in a first aspect, wherein the olefin polymerization catalyst comprises:

[0008] (A) a catalyst solid component, wherein the catalyst solid component comprises titanium, magnesium and an internal electron donor, wherein the internal electron donor comprises a silicon ester compound;

[0009] (B) a co-catalyst component, the co-catalyst component being at least one organoaluminum compound; and

[0010] (C) an external electron donor, the external electron donor comprising a compound represented by formula (I),

[0011]

[0012] In formula (I), any one of R1, R2, R3, R4, and R5 is RO, and the others are the same or different and are independently hydrogen, C1-C 20 A straight chain alkyl or branched chain alkyl, cycloalkyl, aryl, alkaryl, aralkyl, R is selected from C1 to C 20 Preferably, R is selected from C1 to C 20 Straight chain alkyl or branched chain alkyl, C3~C 20 Cycloalkyl, C6~C 10 Aryl, C6~C 10 It can be clearly considered that the compound represented by formula (I) is a phenol and ether bifunctional compound.

[0013] In the present invention, the C1 to C 20 The straight-chain alkyl or branched-chain alkyl may be, for example, methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, tert-pentyl, neopentyl, hexyl, isohexyl, heptyl, isoheptyl, octyl, isooctyl, nonyl, isononyl, decyl, isodecyl, etc. The C6-C 10 The aryl group may be, for example, phenyl, o-tolyl, m-tolyl, p-tolyl, o-ethylphenyl, m-ethylphenyl, p-ethylphenyl or naphthyl. 20The cycloalkyl group may be, for example, cyclopentyl, cyclohexyl, or the like.

[0014] According to a specific embodiment of the present invention, the compound of general formula (I) is preferably selected from at least one of p-methoxyphenol, o-methoxyphenol, m-methoxyphenol, p-ethoxyphenol, o-ethoxyphenol, m-ethoxyphenol, p-propoxyphenol, o-propoxyphenol, m-propoxyphenol, p-butoxyphenol, o-butoxyphenol, m-butoxyphenol, p-hexyloxyphenol, o-hexyloxyphenol, m-hexyloxyphenol, p-octyloxyphenol, o-octyloxyphenol, m-octyloxyphenol, p-nonyloxyphenol, m-nonyloxyphenol, o-nonyloxyphenol, dodecyloxyphenol, tetradecyloxyphenol, octadecyloxyphenol, phenoxyphenol or hydroxyphenyl benzyl ether.

[0015] According to the present invention, preferably, the general formula of the silicone ester compound is R 2 x R 3 y Si(OR 4 ) z , where R 2 and R 3 Each independently is C1~C 10 The hydrocarbon or halogen, R 4 C1~C 10 A hydrocarbon group, wherein x, y, z are positive integers, 0≤x≤2, 0≤y≤2 and 0≤z≤4, and x+y+z=4.

[0016] According to a specific embodiment of the present invention, the silicone ester compound is preferably selected from tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, tetrabutoxysilane, tetra(2-ethylhexyloxy)silane, ethyltrimethoxysilane, ethyltriethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, n-propyltriethoxysilane, n-propyltrimethoxysilane, decyltrimethoxysilane, decyltriethoxysilane, cyclopentyltrimethoxysilane, cyclopentyltriethoxysilane, 2-methylcyclopentyltrimethoxysilane, 2,3-dimethyl Cyclopentyltrimethoxysilane, cyclohexyltrimethoxysilane, cyclohexyltriethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, tert-butyltriethoxysilane, n-butyltrimethoxysilane, n-butyltriethoxysilane, isobutyltrimethoxysilane, isobutyltriethoxysilane, cyclohexyltriethoxysilane, cyclohexyltrimethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, monochlorotrimethoxysilane, monochlorotriethoxysilane , ethyl triisopropoxysilane, vinyl tributoxysilane, trimethylphenoxysilane, methyl triallyloxysilane, vinyl triacetoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, diisopropyldimethoxysilane, diisopropyldiethoxysilane, tert-butylmethyldimethoxysilane, tert-butylmethyldiethoxysilane, tert-amylmethyldiethoxysilane, dicyclopentyldimethoxysilane, dicyclopentyldiethoxysilane, methylcyclopentyldiethoxysilane, methylcyclopentyldimethoxysilane, diphenyldimethoxy Silane, diphenyldiethoxysilane, methylphenyldiethoxysilane, methylphenyldimethoxysilane, bis-o-tolyldimethoxysilane, bis-o-tolyldiethoxysilane, bis-m-tolyldimethoxysilane, bis-m-tolyldiethoxysilane, bis-p-tolyldimethoxysilane, bis-p-tolyldiethoxysilane, trimethylmethoxysilane, trimethylethoxysilane, tricyclopentylmethoxysilane, tricyclopentylethoxysilane, dicyclopentylmethylmethoxysilane and cyclopentyldimethylmethoxysilane are used in combination or in combination.

[0017] More preferably, the silicon ester compound is selected from at least one of tetramethoxysilane, tetraethoxysilane and tetrabutoxysilane.

[0018] According to the present invention, although the internal electron donor in the solid component of the olefin polymerization catalyst contains the silicone ester compound described in the present invention and the external electron donor contains the compound of general formula (I) described in the present invention, the purpose of the present invention can be achieved. However, preferably, in order to better achieve the purpose of the present invention, in the solid component of the olefin polymerization catalyst, the internal electron donor is 0.1 to 1 mole and the titanium is 1 to 25 moles per mole of magnesium. Preferably, the internal electron donor is 0.1 to 0.8 mole and the titanium is 1 to 15 moles.

[0019] According to the present invention, the type and amount of the organoaluminum compound can be selected conventionally in the art. For example, the general formula of the organoaluminum compound is AlR 1 e X 1 f H g , where R 1 is hydrogen or C l ~C 20 Hydrocarbon, X 1 is a halogen atom, preferably fluorine, chlorine or bromine, a, b, c are each independently an integer of 0 to 3, and e+f+g=3. Specifically, examples of the organoaluminum compound include, but are not limited to: AlEt3, Al(iso-Bu)3, Al(n-C6H 13 )3. Al(n-C8H 17 )3 and at least one of AlEt2Cl.

[0020] According to the present invention, the molar ratio of the (B) co-catalyst component calculated as aluminum to the (A) catalyst solid component calculated as titanium is (5-500) 1, preferably (20-200): 1, for example, it can be 5: 1, 10: 1, 20: 1, 50: 1, 100: 1, 150: 1, 200: 1, 250: 1, 300: 1, 350: 1, 400: 1, 450: 1, 500: 1, etc.; The molar ratio of the (C) external electron donor to the (A) catalyst solid component calculated as titanium is (0.05-50):1, preferably (0.1-10):1, for example, it can be 0.05:1, 0.1:1, 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 20:1, 30:1, 40:1, 50:1, etc.

[0021] According to the present invention, the olefin polymerization catalyst solid component (A) can be prepared by various conventional methods in the art, preferably by reacting an alkoxy magnesium compound, an internal electron donor silicon ester compound and a titanium halide and / or its derivatives.

[0022] According to a preferred embodiment of the present invention, the method for preparing the olefin polymerization catalyst solid component (A) comprises the following steps:

[0023] (1) dispersing an alkoxy magnesium compound in an inert solvent under stirring to form a suspension;

[0024] (2) Under stirring, the suspension is contacted with an internal electron donor silicon ester compound and a transition metal titanium halide and / or its derivative for reaction, followed by solid-liquid separation and washing.

[0025] According to the present invention, the alkoxy magnesium compound can be various solid substances containing magnesium commonly used in the field of olefin polymerization catalysts. Preferably, the general formula of the alkoxy magnesium compound is Mg(OR7): a (OR8) 2-a , wherein R7 and R8 are each independently substituted or unsubstituted C1 to C 10 Alkyl, the substituent is selected from at least one of hydroxyl, amino, aldehyde, carboxyl, acyl, halogen, alkoxy and heteroatom, 0≤a≤2.

[0026] According to a specific embodiment of the present invention, non-limiting examples of the alkoxy magnesium compound include: Mg(OEt)2, Mg(OCH2CH2CH3)2, Mg(OBu)2, 2-octyloxy magnesium, Mg(OEt) a (OEHA) 2-a (1.5≤a≤2) and Mg(OEt) a (OBu) 2-a (1.3≤a≤2) or more, wherein EHA is 2-ethylhexyl. More preferably, the alkoxy magnesium compound is Mg(OEt)2 and / or Mg(OEt) a (OEHA) 2-a (1.5≤a≤2).

[0027] According to the present invention, the amount of the inert solvent can be selected according to the amount of the alkoxy magnesium compound. Generally, based on 1 mol of the alkoxy magnesium compound, the amount of the inert solvent is 0.8 to 10 L, preferably 2 to 8 L. The inert solvent can be various liquid media commonly used in the art that do not chemically interact with the reactants and reaction products. For example: the inert solvent can be silicone oil and / or an inert liquid hydrocarbon solvent. Specifically, the inert solvent can be one or more of toluene, kerosene, paraffin oil, vaseline oil, white oil, methyl silicone oil, ethyl silicone oil, methylethyl silicone oil, phenyl silicone oil and methylphenyl silicone oil.

[0028] According to the present invention, the suspension is contacted with an internal electron donor silicon ester compound and a transition metal titanium halide and / or its derivative under stirring in the same manner as in the prior art, except that the internal electron donor is a silicon ester compound provided by the present invention. For example, the suspension can be mixed with the silicon ester compound, the transition metal titanium halide and / or its derivative for reaction at -30°C to 0°C for 30 to 180 minutes, then heated to 50 to 120°C, and maintained at the reaction temperature for 0.5 to 10 hours, then solid-liquid separation and washing are performed to obtain the olefin polymerization catalyst solid component.

[0029] Preferably, the addition ratio of the alkoxy magnesium compound, the silicon ester compound and the halide of transition metal titanium and / or its derivatives is, per mole of alkoxy magnesium, the amount of the internal electron donor silicon ester compound is 0.1 to 1 mole, and the amount of the halide of transition metal titanium and / or its derivatives is 1 to 25 moles. Preferably, the amount of the internal electron donor silicon ester compound is 0.1 to 0.8 mole, and the amount of the halide of transition metal titanium and / or its derivatives is 1 to 15 moles. Specifically, per mole of magnesium, the internal electron donor can be 0.1 mole, 0.2 mole, 0.3 mole, 0.4 mole, 0.5 mole, 0.6 mole, 0.7 mole, 0.8 mole, 0.9 mole, 1 mole, etc., and the halide of titanium and / or its derivatives can be 1 mole, 5 moles, 10 moles, 15 moles, 20 moles, 25 moles, etc.

[0030] According to the present invention, the transition metal titanium halide and / or its derivatives can be various titanium-containing substances commonly used in the field of olefin polymerization catalysts. Preferably, the transition metal titanium halide or its derivative has the general formula of Ti(OR9): d X b , where R9 is C1~C 14 The hydrocarbon group is preferably a C1-C8 alkyl group; X is a halogen atom, d and b are each independently an integer of 1-4, and d+b=3 or 4.

[0031] Specifically, the C1-C8 alkyl group may be, for example, methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, tert-pentyl, neopentyl, hexyl, isohexyl, heptyl, isoheptyl, octyl, isooctyl, etc. Non-limiting examples of the transition metal titanium halide and / or its derivatives include: one or more of TiCl3, TiCl4, TiBr4, TiCl4, Ti(OC2H5)Cl3, Ti(OCH3)Cl3, Ti(OC4H9)Cl3, Ti(OC2H5)Br3, Ti(OC2H5)2Cl2, Ti(OCH3)2Cl2, Ti(OCH3)2I2, Ti(OC2H5)3Cl, Ti(OCH3)3Cl, Ti(OC2H5)3I, Ti(OC2H5)4, Ti(OC3H7)4, and Ti(OC4H9)4. Preferably, the transition metal titanium halide and / or its derivative is selected from one or more of TiCl3, TiCl4, TiBr4, Ti(OC2H5)2Cl2, Ti(OC2H5)Cl3, Ti(OC2H5)3Cl, Ti(OCH3)Cl3, Ti(OC4H9)Cl3 and Ti(OC4H9)4. In a specific embodiment of the present invention, TiCl4 is preferred.

[0032] Preferably, in order to better improve the activity and copolymerization performance of the olefin polymerization catalyst, in step (2), the transition metal titanium halide and / or its derivative is added in multiple times, more preferably in two times, and a certain contact reaction time is ensured, so as to further improve the hydrogen sensitivity and polymerization activity of the olefin polymerization catalyst. Specifically, the contact reaction method comprises:

[0033] (a) reacting a suspension with a first transition metal titanium halide and / or its derivative at a temperature of -30°C to 0°C, and adding an internal electron donor silicon ester compound in one or more time periods before, during and after the reaction of the suspension with the transition metal titanium halide and / or its derivative to obtain a first product;

[0034] (b) The first product obtained in step (1) is heated to 50-120° C., reacted under stirring conditions for 0.5-4 hours, then allowed to stand, separated into layers, and the supernatant liquid is removed, and the second product obtained is contacted with a second transition metal titanium halide and / or its derivative and an inert solvent optionally added, and reacted under stirring for 0.5-4 hours, and then the solid-liquid separation and washing are performed.

[0035] According to the present invention, in step (a), preferably, the suspension and the first transition metal titanium halide and / or its derivative are stirred and mixed for reaction at -30°C to 0°C for 10 to 60 minutes, and the internal electron donor silicon ester compound is added in one or more time periods before, during and after the reaction of the suspension with the transition metal titanium halide and / or its derivative, preferably in the time period before the reaction of the suspension with the first transition metal titanium halide and / or its derivative. The time period before the reaction of the suspension with the first transition metal titanium halide and / or its derivative refers to the time period after the suspension is added to the reactor and before the temperature is raised to the reaction temperature of step (b).

[0036] According to the present invention, although the hydrogen adjustment sensitivity and polymerization activity of the solid component of the olefin polymerization catalyst under high hydrogen conditions can be improved by adding the transition metal titanium halide and / or its derivatives in multiple times, more preferably adding the transition metal titanium halide and / or its derivatives in two times and ensuring a certain contact reaction time and controlling a certain temperature rise trend, the obtained olefin polymerization catalyst exhibits high catalytic activity, good hydrogen adjustment sensitivity and good copolymerization performance when used for ethylene polymerization. However, in order to make the treatment effect more significant and obtain the olefin polymerization catalyst solid component and olefin polymerization catalyst with better comprehensive performance, preferably, in step (a), the amount of the silicon ester compound is 0.1 to 1 mole per mole of alkoxy magnesium, and the amount of the first transition metal titanium halide and its derivative is 1 to 20 moles. The molar ratio of the second transition metal titanium halide and its derivatives to the first transition metal titanium halide and its derivatives can be selected within a wide range. More preferably, in order to better achieve the above-mentioned purpose, the molar ratio of the second transition metal titanium halide and its derivatives to the first transition metal titanium halide and its derivatives is 1:(1 to 5).

[0037] According to the present invention, the method for solid-liquid separation of the final product obtained in step (b) can be any existing method capable of achieving solid-liquid separation, such as suction filtration, filter press or centrifugal separation. Preferably, the solid-liquid separation method is filter press. The present invention does not particularly limit the conditions for filter press, so long as the separation of the solid and liquid phases is achieved as fully as possible.

[0038] According to the present invention, in step (b), in order to make the reaction more fully proceed, the step (b) can also be carried out in the presence of an inert solvent, and the amount of the inert solvent can be conventionally selected according to the amount of the second product and the second transition metal titanium halide and / or its derivative. The inert solvent can be silicone oil and / or an inert liquid hydrocarbon solvent. Specifically, the inert solvent can be one or more of toluene, kerosene, paraffin oil, vaseline oil, white oil, methyl silicone oil, ethyl silicone oil, methylethyl silicone oil, phenyl silicone oil and methylphenyl silicone oil.

[0039] According to the present invention, when the olefin polymerization catalyst is applied to a polymerization reaction, (A), (B) and (C) can be mixed in various conventional ways in the art. For example, according to one specific embodiment, any two components of (A), (B) and (C) can be pre-mixed and then mixed with another component (specifically, (A) and (C) can be mixed before adding (B)); according to another specific embodiment, (A), components (B) and (C) can be mixed simultaneously.

[0040] The second aspect of the present invention provides use of the olefin polymerization catalyst of the present invention in ethylene homopolymerization and / or copolymerization.

[0041] The olefin polymerization catalyst provided by the present invention is suitable for homopolymerization of ethylene or copolymerization of ethylene and other α-olefins, wherein the α-olefin can be selected from at least one of propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, and 4-methylpentene-1. During the polymerization, slurry polymerization or gas phase polymerization can be adopted, and the polymerization temperature can be 0 to 150° C., preferably 60 to 90° C.

[0042] The slurry polymerization medium includes inert solvents such as isobutane, hexane, heptane, cyclohexane, naphtha, raffinate, hydrogenated gasoline, kerosene, benzene, toluene, xylene and other saturated aliphatic hydrocarbons or aromatic hydrocarbons.

[0043] In order to adjust the molecular weight of the final polymer, hydrogen can also be used as a molecular weight regulator.

[0044] The olefin polymerization catalyst provided by the present invention is added with an internal electron donor silicon ester compound and an external electron donor compound of the general formula (I), so that the obtained olefin polymerization catalyst can not only show good activity and copolymerization performance, but also can show high polymerization activity and high polymer melt index under polymerization conditions of high hydrogen-ethylene ratio (for example, hydrogen partial pressure: ethylene partial pressure ≥ 3), and show low polymer melt index under polymerization conditions of low hydrogen-ethylene ratio (for example, hydrogen partial pressure: hydrogen partial pressure: ethylene partial pressure ≤ 1). When the olefin polymerization catalyst provided by the present invention is used for ethylene polymerization, it shows high catalytic activity and more suitable hydrogen adjustment sensitivity. The solid component of the olefin polymerization catalyst provided by the present invention and the preparation process of the olefin polymerization catalyst are simple, and are very suitable for ethylene slurry polymerization process with two or more kettles in series.

[0045] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION

[0046] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the content of the present invention still fall within the scope of protection of the present invention.

[0047] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0048] The experimental test methods in the following embodiments and comparative examples include:

[0049] 1. Relative weight percentage of titanium element in solid catalyst component: by spectrophotometry.

[0050] 2. Polymer melt index (MI): determined according to ASTM D1238-99, load 2.16 kg, 190°C.

[0051] Example 1

[0052] This example is used to illustrate the olefin polymerization catalyst and polymerization reaction provided by the present invention.

[0053] (1) Preparation of solid catalyst components

[0054] In a reactor fully replaced with high-purity nitrogen, add 4.8g of ethoxymagnesium and 60mL of toluene in sequence to form a suspension under a stirring speed of 300rpm. Cool the system to -20℃, add 4ml of ethyl orthosilicate, and then drop 40mL of titanium tetrachloride. After keeping the temperature constant for 30 minutes, heat it to 80℃ and react for 2 hours. Stop stirring, let it stand, the suspension will quickly separate into layers, and remove the supernatant. Add 60mL of toluene and 20mL of titanium tetrachloride, heat it to 80℃, and keep the temperature constant for 2 hours. Stop stirring, let it stand, and remove the supernatant. After washing with toluene and hexane for several times and drying, a catalyst solid component A1 with good fluidity is obtained.

[0055] (2) Homopolymerization

[0056] ①Polymerization reaction with low hydrogen / ethylene ratio

[0057] A stainless steel reactor with a volume of 2L was fully replaced with high-purity nitrogen, and then 1L of hexane and 1.0mL of 1M triethylaluminum were added, and then the catalyst solid component A1 (containing 0.4mg titanium) prepared by the above method and p-methoxyphenol were added, and the molar ratio of p-methoxyphenol to catalyst Ti was 1:1. The temperature was raised to 70°C, hydrogen was introduced to make the pressure in the reactor reach 0.28MPa, and ethylene was introduced to make the total pressure in the reactor reach 0.73MPa. Polymerization was carried out at 80°C for 2 hours. The polymerization results are shown in Table 1.

[0058] ②Polymerization reaction with high hydrogen / ethylene ratio

[0059] A stainless steel reactor with a volume of 2L was fully replaced with high-purity nitrogen, and then 1L of hexane and 1.0mL of 1M triethylaluminum were added, and then the catalyst solid component A1 (containing 0.4mg titanium) prepared by the above method and p-methoxyphenol were added, and the molar ratio of p-methoxyphenol to catalyst Ti was 1:1. The temperature was raised to 70°C, hydrogen was introduced to make the pressure in the reactor reach 0.58MPa, and ethylene was introduced to make the total pressure in the reactor reach 0.73MPa. Polymerization was carried out at 80°C for 2 hours. The polymerization results are shown in Table 2.

[0060] Example 2

[0061] This example is used to illustrate the olefin polymerization catalyst and polymerization reaction provided by the present invention.

[0062] (1) Preparation of solid catalyst components

[0063] An olefin polymerization catalyst solid component was prepared according to the method of Example 1 to obtain a catalyst solid component A2.

[0064] (2) Homopolymerization

[0065] Homopolymerization was carried out according to the method of Example 1, except that p-methoxyphenol was replaced by p-ethoxyphenol, and the molar ratio of p-ethoxyphenol added to catalyst Ti was 1:1. The polymerization results are shown in Tables 1 and 2, respectively.

[0066] Example 3

[0067] This example is used to illustrate the olefin polymerization catalyst and polymerization reaction provided by the present invention.

[0068] (1) Preparation of solid catalyst components

[0069] An olefin polymerization catalyst solid component was prepared according to the method of Example 1 to obtain a catalyst solid component A3.

[0070] (2) Homopolymerization

[0071] Homopolymerization was carried out according to the method of Example 1, except that p-methoxyphenol was replaced by p-butoxyphenol. The polymerization results are shown in Tables 1 and 2.

[0072] Example 4

[0073] This example is used to illustrate the olefin polymerization catalyst and polymerization reaction provided by the present invention.

[0074] (1) Preparation of solid catalyst components

[0075] An olefin polymerization catalyst solid component was prepared according to the method of Example 1 to obtain a catalyst solid component A4.

[0076] (2) Homopolymerization

[0077] Homopolymerization was carried out according to the method of Example 1, except that the amount of p-methoxyphenol added was adjusted so that the molar ratio of p-methoxyphenol to Ti in the catalyst was 1.5:1. The polymerization results are shown in Tables 1 and 2, respectively.

[0078] Example 5

[0079] This example is used to illustrate the olefin polymerization catalyst and polymerization reaction provided by the present invention.

[0080] (1) Preparation of solid catalyst components

[0081] An olefin polymerization catalyst solid component was prepared according to the method of Example 1 to obtain a catalyst solid component A5.

[0082] (2) Homopolymerization

[0083] Homopolymerization was carried out according to the method of Example 2, except that the molar ratio of the amount of ethoxyphenol added to the Ti in the catalyst was 1.5:1. The polymerization results are shown in Tables 1 and 2.

[0084] Example 6

[0085] This example is used to illustrate the olefin polymerization catalyst and polymerization reaction provided by the present invention.

[0086] (1) Preparation of solid catalyst components

[0087] An olefin polymerization catalyst solid component was prepared according to the method of Example 1 to obtain a catalyst solid component A6.

[0088] (2) Homopolymerization

[0089] Homopolymerization was carried out according to the method of Example 3, except that the molar ratio of the amount of p-butoxyphenol added to the Ti in the catalyst was adjusted to 1.5:1. The polymerization results are shown in Tables 1 and 2.

[0090] Example 7

[0091] This example is used to illustrate the olefin polymerization catalyst and polymerization reaction provided by the present invention.

[0092] (1) Preparation of solid catalyst components

[0093] An olefin polymerization catalyst solid component was prepared according to the method of Example 1 to obtain a catalyst solid component A7.

[0094] (2) Homopolymerization

[0095] Homopolymerization was carried out according to the method of Example 1, except that the amount of p-methoxyphenol added was adjusted so that the molar ratio of p-methoxyphenol to Ti in the catalyst was 2:1. The polymerization results are shown in Tables 1 and 2.

[0096] Example 8

[0097] This example is used to illustrate the olefin polymerization catalyst and polymerization reaction provided by the present invention.

[0098] (1) Preparation of solid catalyst components

[0099] An olefin polymerization catalyst solid component was prepared according to the method of Example 1 to obtain a catalyst solid component A8.

[0100] (2) Homopolymerization

[0101] Homopolymerization was carried out according to the method of Example 2, except that the molar ratio of the amount of p-ethoxyphenol added to the Ti in the catalyst was 2:1. The polymerization results are shown in Tables 1 and 2.

[0102] Example 9

[0103] This example is used to illustrate the olefin polymerization catalyst and polymerization reaction provided by the present invention.

[0104] (1) Preparation of solid catalyst components

[0105] An olefin polymerization catalyst solid component was prepared according to the method of Example 1 to obtain a catalyst solid component A9.

[0106] (2) Homopolymerization

[0107] Homopolymerization was carried out according to the method of Example 1, except that the molar ratio of the amount of p-butoxyphenol added to the Ti in the catalyst was 2:1. The polymerization results are shown in Tables 1 and 2.

[0108] Example 10

[0109] This example is used to illustrate the preparation of the solid component of the olefin polymerization catalyst provided by the present invention and the polymerization reaction using the olefin polymerization catalyst obtained thereby.

[0110] (1) Preparation of Olefin Polymerization Catalyst Solid Component A10

[0111] In a reactor fully replaced with high-purity nitrogen, 4.8g of ethoxymagnesium and 60mL of toluene were added in sequence to form a suspension under a stirring speed of 300rpm. The system was cooled to -20°C, 3.5ml of ethyl orthosilicate was added in sequence, and 60mL of titanium tetrachloride was added dropwise. After the temperature was kept constant for 30 minutes, the temperature was raised to 80°C and the reaction was carried out for 2 hours. Stirring was stopped, the suspension was allowed to stand, and the suspension was quickly separated into layers. The upper clear liquid was removed. 60mL of toluene and 40mL of titanium tetrachloride were added, the temperature was raised to 80°C, and the temperature was kept constant for 2 hours. Stirring was stopped, the suspension was allowed to stand, and the upper clear liquid was removed. After being washed with toluene and hexane for several times and dried, a solid component A10 of olefin polymerization catalyst with good fluidity was obtained.

[0112] (2) Homopolymerization

[0113] Homopolymerization was carried out according to the method of Example 1, except that the catalyst solid component A10 (containing 0.4 mg titanium) prepared by the above method and p-methoxyphenol were added, and the molar ratio of the amount of p-methoxyphenol added to the catalyst Ti was 1:1. The amount of triethylaluminum added was adjusted to 2 ml. The polymerization results are shown in Tables 1 and 2, respectively.

[0114] Comparative Example 1

[0115] This comparative example is used to illustrate the preparation of a reference olefin polymerization catalyst and a polymerization reaction.

[0116] (1) Preparation of Catalyst Solid Component C

[0117] In a reactor fully replaced with high-purity nitrogen, 4.8g of ethoxymagnesium and 60mL of toluene were added in sequence to form a suspension under a stirring speed of 300rpm. The system was cooled to -20°C, 40mL of titanium tetrachloride was slowly added dropwise, and after keeping the temperature constant for 30 minutes, the temperature was raised to 80°C and the reaction was carried out for 2 hours. Stirring was stopped, the suspension was allowed to stand, and the suspension was quickly separated into layers, and the supernatant was removed. 60mL of toluene and 20mL of titanium tetrachloride were added, the temperature was raised to 80°C, and the temperature was kept constant for 2 hours. Stirring was stopped, the temperature was stood, and the supernatant was removed. After being washed with toluene and hexane for many times and dried, a solid component C of an olefin polymerization catalyst with good fluidity was obtained, and its composition is shown in Table 1.

[0118] (2) Homopolymerization

[0119] Homopolymerization was carried out according to the method of Example 1, except that the olefin polymerization catalyst solid component was the olefin polymerization catalyst solid component C prepared in this comparative example and no external electron donor was added. The polymerization results are shown in Tables 1 and 2.

[0120] Comparative Example 2

[0121] This comparative example is used to illustrate the preparation of a reference olefin polymerization catalyst and a polymerization reaction.

[0122] (1) Preparation of catalyst solid component D

[0123] In a reactor fully replaced with high-purity nitrogen, add 4.8g of ethoxymagnesium and 60mL of toluene in sequence to form a suspension under a stirring speed of 300rpm. Cool the system to -20℃, add 4ml of ethyl orthosilicate, slowly drip 40mL of titanium tetrachloride, keep constant temperature for 30 minutes, then raise the temperature to 80℃ and react for 2 hours. Stop stirring, let it stand, the suspension will quickly separate into layers, and remove the supernatant. Add 60mL of toluene and 20mL of titanium tetrachloride, raise the temperature to 80℃, and keep constant temperature for 2 hours. Stop stirring, let it stand, and remove the supernatant. After washing with toluene and hexane for many times and drying, a solid component D of olefin polymerization catalyst with good fluidity is obtained.

[0124] (2) Homopolymerization

[0125] Homopolymerization was carried out according to the method of Example 1, except that the olefin polymerization catalyst solid component was the olefin polymerization catalyst solid component D prepared in this comparative example and no external electron donor was added. The polymerization results are shown in Tables 1 and 2.

[0126] Table 1

[0127]

[0128] It can be seen from the data in Table 1 that after adding the internal electron donor tetraethyl orthosilicate and the external electron donor compound of the general formula (I), the catalyst of the present invention has good activity and titanium content under low hydrogen polymerization conditions. At the same time, with the addition of the external electron donor compound of the general formula (I), the catalyst exhibits the characteristics of low hydrogen and low melt index.

[0129] Table 2

[0130]

[0131] From the data in Table 2, it can be seen that after adding the internal electron donor silicon ester compound and the external electron donor compound of the general formula (I), the activity and hydrogen adjustment sensitivity of the catalyst of the present invention under high hydrogen polymerization conditions are significantly better than those of the comparative example. It can be seen that the combined effect of the compound of the general formula (I) and the silicon ester compound enables the catalyst to have a large increase in the melt index of the obtained polymer under the condition of a higher hydrogen-to-ethyl ratio, and a smaller melt index under the condition of a lower hydrogen-to-ethyl ratio. This feature is conducive to the production of bimodal polyethylene products in the slurry polymerization process and the production of high melt index products in the gas phase polymerization process.

[0132] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

[0133] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

Claims

1. An olefin polymerization catalyst comprising: (A) a catalyst solid component, wherein the catalyst solid component comprises titanium, magnesium and an internal electron donor, wherein the internal electron donor comprises a silicon ester compound, wherein the silicon ester compound has a general formula of R 2 x R 3 y Si(OR 4 ) z , where R 2 and R 3 Each is independently C1~C 10 Hydrocarbon or halogen, R 4 C1~C 10 A hydrocarbon group, wherein x, y, and z are positive integers, 0 ≤ x ≤ 2, 0 ≤ y ≤ 2, 0 ≤ z ≤ 4, and x + y + z = 4; (B) a co-catalyst component, wherein the co-catalyst component is at least one organoaluminum compound, wherein the general formula of the organoaluminum compound is AlR 1 e X 1 f H g , where R 1 is hydrogen or C l ~C 20 Hydrocarbon, X 1 is a halogen atom, e, f, and g are each independently an integer of 0 to 3, and e+f+g=3; and (C) an external electron donor, wherein the external electron donor comprises a compound represented by formula (I), (I), In formula (I), any one of R1, R2, R3, R4, and R5 is RO, and the others are the same or different and are independently C1 to C 20 A straight chain alkyl or branched chain alkyl, cycloalkyl, aryl, alkaryl, aralkyl, R is selected from C1~C 20 A straight-chain alkyl group or a branched-chain alkyl group, a cycloalkyl group, an aryl group, an alkaryl group, or an aralkyl group; Calculated per mole of magnesium, the internal electron donor is 0.1 to 1 mole, and the titanium is 1 to 25 moles; the molar ratio of the co-catalyst component calculated in terms of aluminum to the catalyst solid component calculated in terms of titanium is (5 to 500):1; the molar ratio of the external electron donor to the catalyst solid component calculated in terms of titanium is (0.05 to 50):

1.

2. The olefin polymerization catalyst according to claim 1, characterized in that: The silicone ester compound is selected from tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, tetrabutoxysilane, tetra(2-ethylhexyloxy)silane, ethyltrimethoxysilane, ethyltriethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, n-propyltriethoxysilane, n-propyltrimethoxysilane, decyltrimethoxysilane, decyltriethoxysilane, cyclopentyltrimethoxysilane, cyclopentyltriethoxysilane, 2-methylcyclopentyltrimethoxysilane, 2,3-dimethoxysilane, 2-methylcyclopentyltrimethoxysilane, 2,3-dimethoxysilane, 2-methylcyclopentyltrimethoxysilane, 2,3-dimethoxysilane, 2-methylcyclopentyltrimethoxysilane, 2,3-dimethoxysilane, 2-methylcyclopentyltrimethoxysilane, 2,3-dimethoxysilane, 2-methylcyclopentyltriethoxysilane, 2,3-dimethoxysilane, 2-methylcyclopentyltrimeth ...ethoxysilane, 2-methylcyclopentyltrimethoxysilane, 2,3-dimethoxysilane, 2-methylcyclopentyltrimethoxysilane, 2,3-dimethoxysilane, 2-propyltriethoxysilane, 2-propyltriethoxysilane, 2-propyltriethoxysilane, 2-propyltriethoxysilane, 2-propyltriethoxysilane, 2- Methylcyclopentyltrimethoxysilane, cyclohexyltrimethoxysilane, cyclohexyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, tert-butyltriethoxysilane, n-butyltrimethoxysilane, n-butyltriethoxysilane, isobutyltrimethoxysilane, isobutyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, monochlorotrimethoxysilane, monochlorotriethoxysilane, ethyltriisopropoxysilane, vinyltributoxysilane, trimethylphenoxy Silane, methyl triallyloxysilane, vinyl triacetoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, diisopropyldimethoxysilane, diisopropyldiethoxysilane, tert-butylmethyldimethoxysilane, tert-butylmethyldiethoxysilane, tert-amylmethyldiethoxysilane, dicyclopentyldimethoxysilane, dicyclopentyldiethoxysilane, methylcyclopentyldiethoxysilane, methylcyclopentyldimethoxysilane, diphenyldimethoxysilane, diphenyldiethoxy At least one of silane, methylphenyldiethoxysilane, methylphenyldimethoxysilane, bis-o-tolyldimethoxysilane, bis-o-tolyldiethoxysilane, bis-m-tolyldimethoxysilane, bis-m-tolyldiethoxysilane, bis-p-tolyldimethoxysilane, bis-p-tolyldiethoxysilane, trimethylmethoxysilane, trimethylethoxysilane, tricyclopentylmethoxysilane, tricyclopentylethoxysilane, dicyclopentylmethylmethoxysilane, and cyclopentyldimethylmethoxysilane.

3. The olefin polymerization catalyst according to claim 1, characterized in that: In the general formula of the organoaluminum compound, X 1 is fluorine, chlorine or bromine.

4. The olefin polymerization catalyst according to claim 1, characterized in that: The organic aluminum compound is selected from AlEt3, Al(iso-Bu)3, Al(n-C6H 13 )3. Al(n-C8H 17 )3. At least one of AlEt2Cl.

5. The olefin polymerization catalyst according to claim 1, characterized in that: The compound represented by formula (I) is at least one selected from p-methoxyphenol, o-methoxyphenol, m-methoxyphenol, p-ethoxyphenol, o-ethoxyphenol, m-ethoxyphenol, p-propoxyphenol, o-propoxyphenol, m-propoxyphenol, p-butoxyphenol, o-butoxyphenol, m-butoxyphenol, p-hexyloxyphenol, o-hexyloxyphenol, m-hexyloxyphenol, p-octyloxyphenol, o-octyloxyphenol, m-octyloxyphenol, p-nonyloxyphenol, m-nonyloxyphenol, o-nonyloxyphenol, dodecyloxyphenol, tetradecyloxyphenol, octadecyloxyphenol, phenoxyphenol, and hydroxyphenyl benzyl ether.

6. The olefin polymerization catalyst according to claim 1, characterized in that: For every mole of magnesium, the internal electron donor is 0.1 to 0.8 moles and the titanium is 1 to 15 moles; The molar ratio of the co-catalyst component calculated in terms of aluminum to the catalyst solid component calculated in terms of titanium is (20-200):1; The molar ratio of the external electron donor to the catalyst solid component calculated as titanium is (0.1-10):

1.

7. The olefin polymerization catalyst according to any one of claims 1 to 6, characterized in that The catalyst solid component is prepared by the following steps: (1) dispersing an alkoxy magnesium compound in an inert solvent to form a suspension; (2) The suspension is contacted with an internal electron donor and a titanium halide and / or a derivative thereof for reaction, followed by solid-liquid separation.

8. The olefin polymerization catalyst according to claim 7, characterized in that: The general formula of the alkoxy magnesium compound is Mg(OR7) a (OR8) 2-a , wherein R7 and R8 are each independently substituted or unsubstituted C1~C 10 Alkyl, the substituent is selected from at least one of hydroxyl, amino, aldehyde, carboxyl, acyl, halogen, alkoxy and heteroatom, 0≤a≤2; The general formula of the titanium halide or its derivative is Ti(OR9) d X b , where R9 is C1~C 14 A hydrocarbon group; X is a halogen atom, d and b are each independently an integer of 1 to 4, and d+b=3 or 4.

9. The olefin polymerization catalyst according to claim 8, characterized in that: The alkoxy magnesium compound is selected from Mg(OEt)2, Mg(OCH2CH2CH3)2, Mg(OBu)2, 2-octyloxy magnesium, Mg(OEt) a (OEHA) 2-a 、Mg(OEt) a (OBu) 2-a At least one of, wherein EHA is 2-ethylhexyl; In the general formula of the titanium halide or its derivative, R9 is a C1-C8 alkyl group.

10. The olefin polymerization catalyst according to claim 9, characterized in that: The titanium halide or its derivative is selected from at least one of TiCl3, TiCl4, TiBr4, Ti(OC2H5)Cl3, Ti(OCH3)Cl3, Ti(OC4H9)Cl3, Ti(OC2H5)Br3, Ti(OC2H5)2Cl2, Ti(OCH3)2Cl2, Ti(OCH3)2I2, Ti(OC2H5)3Cl, Ti(OCH3)3Cl, Ti(OC2H5)3I, Ti(OC2H5)4, Ti(OC3H7)4, and Ti(OC4H9)4.

11. The olefin polymerization catalyst according to claim 7, characterized in that In step (2), the contact reaction method comprises: (a) reacting a suspension with a first titanium halide and / or a derivative thereof at a temperature of -30°C to 0°C, and adding an internal electron donor at one or more time periods before, during and after the reaction of the suspension with the titanium halide and / or a derivative thereof to obtain a first product; (b) The first product obtained in step (a) is heated to 50-120° C., reacted under stirring, then allowed to stand, separated into layers, and the supernatant is removed to obtain a second product, and the obtained second product is contacted with a second titanium halide and / or its derivative and an inert solvent that is optionally added and reacted under stirring, and then the solid-liquid separation is carried out.

12. The olefin polymerization catalyst according to claim 11, characterized in that: In step (a), the amount of the internal electron donor is 0.1 to 1 mole, and the amount of the first titanium halide and / or derivative is 1 to 20 moles per mole of alkoxy magnesium; In step (b), the molar ratio of the second titanium halide and its derivative to the first titanium halide and / or its derivative is 1:(1-5).

13. Use of the olefin polymerization catalyst according to any one of claims 1 to 12 in ethylene homopolymerization and / or copolymerization.

Citation Information

Patent Citations

  • Process for the preparation of a catalyst component and components therefrom obtained

    CN101050248A

  • Catalyst system for ethylene polymerization

    CN102977232A

  • Catalyst component for polymerization or copolymerization of ethylene and catalyst thereof

    CN103772536A

  • Catalyst components for the polymerization of olefins

    CN1726230A

  • Process for the preparation of a catalyst component and components therefrom obtained

    CN1798774A